Pendidikan Kesadaran Kristis: Sebuah Tantangan dalam Pendidikan Agama Kristen - Frets Keriapy; Hendrik Legi; Yoel Giban (Sekolah Tinggi Teologi Simpson Ungaran, 2022)
The conciousness of critical thinking is important and should be concern for every educational institutions in Indonesia. Training students to think critically and analytically on various kinds of problems is a serious thing for educators to do. So the purpose of this research is the education for critical consiousness promoted by Paulo Freire, can be applied in education in Indonesia, in order to produce students who think critically, including in terms of Christian teaching. By using a literature-based qualitative method, the authors systematically and theoretically describe critical conciousness in Christian religious Education. This is a challenge for Christian religious education in responding to it. Therefore, the interaction space between Christian religious education and students’ critical thinking conciousness becomes a meeting room that must be nurtured. So from this research, the authors conclude that to produce critical pedagogy that places social problems becomes central in the discussion room in the classroom.